2011
DOI: 10.1167/iovs.10-6365
|View full text |Cite
|
Sign up to set email alerts
|

Association of Birth Parameters with OCT Measured Macular and Retinal Nerve Fiber Layer Thickness

Abstract: Low birth weight and prematurity are associated with thickening of the fovea, and decreased birth weight is associated with decreased RNFL thickness, as measured by OCT. These findings suggest that premature birth and low birth weight impair retinal development and may predispose these children to ocular problems later in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 31 publications
4
58
1
5
Order By: Relevance
“…This result is in agreement with recent studies using SD-OCT. 1,2,7 With regard to sectoral distributions of peripapillary RNFL, it has been reported that peripapillary RNFL thickness on the temporal side of the disc is thicker in preterm children than in full-term controls, whereas all other peripapillary RNFL sectors are thinner in preterm children than those in full-term children. 1,2 In this study, the results also showed that all peripapillary RNFL sectors except for the temporal side were thinner in preterm children than those in full-term controls. Statistically significant differences were observed in the average total, nasal, and superior disc RNFL thicknesses after adjustment for patients' age at examination and spherical equivalent refractive error.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is in agreement with recent studies using SD-OCT. 1,2,7 With regard to sectoral distributions of peripapillary RNFL, it has been reported that peripapillary RNFL thickness on the temporal side of the disc is thicker in preterm children than in full-term controls, whereas all other peripapillary RNFL sectors are thinner in preterm children than those in full-term children. 1,2 In this study, the results also showed that all peripapillary RNFL sectors except for the temporal side were thinner in preterm children than those in full-term controls. Statistically significant differences were observed in the average total, nasal, and superior disc RNFL thicknesses after adjustment for patients' age at examination and spherical equivalent refractive error.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using optical coherence tomography (OCT) have revealed that preterm children also have a thinner peripapillary retinal nerve fiber layer (RNFL) than children born at term, suggesting an association between prematurity and subclinical optic nerve hypoplasia. 1,2 These studies showed a significant correlation between RNFL thickness and gestational age 1 and birth weight. 2 Because gestational age and birth weight are closely related with each other and are also strongly correlated with development of other disorders including retinal vascular disorder, ROP, it is difficult to determine which factor is a critical contributor for the abnormality in the optic nerve development in prematurity.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been shown that both low birth weight and prematurity have important and significant effects on posterior segment structures, e.g., fovea, macula, retinal nerve fiber layer (RNFL), and optic disc. 22,23 In the study, we examined the association between birth weight and anterior segment structures. Our study population comprised preschool children, born at term, with birth weight of >2500 g. Previous studies had reported that prematurity and low birth weight have significant effects on the anterior segment, particularly in premature infants with/without ROP (Retinopathy of Prematurity).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased birth weight is also associated with decreased retinal nerve fiber layer thickness. 22 These findings suggest that low birth weight may impair retinal nerve fiber layer and corneal development, and may predispose such children to ocular problems, e.g., glaucoma or keratoconus, in later life. Central part of the cornea is the most important area for biomechanics and optics of corneal architecture.…”
Section: Accepted Manuscriptmentioning
confidence: 93%